Strengthening Digital Sharia Financial Literacy through a PAR Approach at Sunan Drajat Islamic Boarding School, Lamongan - Biyati Ahwarumi (Jurnal Insan Pengabdian Indonesia, 2024)
This study aims to evaluate the effectiveness of Islamic financial literacy training based on Participatory Action Research (PAR) in improving students' understanding, skills, and awareness of Islamic financial management according to Islamic principles in the context of digitalization of Islamic boarding school economy. The study was conducted at the Sunan Drajat Islamic Boarding School in Lamongan by involving students and cooperative administrators through three stages: needs assessment, workshop and simulation-based application training, and reflective mentoring. Data were collected through pre-post tests, observations, interviews, and documentation, then analyzed quantitatively and qualitatively. The results showed a significant increase in four indicators of financial literacy, as well as the emergence of microeconomic initiatives pioneered by students. Active involvement of participants is a key factor in success. These findings emphasize the importance of integrating participatory approaches and digital technology in Islamic financial education, as well as its contribution to strengthening the Islamic boarding school economic ecosystem. The limitations of duration and coverage of the area indicate the need for broader and more sustainable follow-up studies.